Minimal use of ICD social determinant or phenomenological codes in mental health care records. (2nd January 2023) - Kinderman, Peter; Allsopp, Kate; Zero, Rosie; Handerer, Fritz; Tai, Sara
Abstract: Background: We have previously argued that psychiatric diagnosis, by focusing on pathology, minimises the role of psychosocial factors. Despite suggestions that traditional diagnosis is the only way to access treatment services, we have recommended standardised use of existing codes for possible social determinants and precise description of psychological phenomena. Aims: This study examines the current use of social determinant and phenomenological codes in mental health care records. Methods: Data provided by a local NHS Trust included 21, 701 cases with a first contact date between 01 January 2015 and 01 January 2016, 4656 of whom received a primary diagnosis. Results: Overall, codes for possible social determinants were used on only 43 occasions, for 39 individuals (0.8% of the 4656 people receiving a primary diagnosis). Comparison with relevant baseline frequencies revealed a highly significant under-reporting of key social determinants. 19 cases (0.4% of 4.656) used codes for precise description of specific psychological phenomena. Conclusions: Available ICD codes for social determinants and specific psychological phenomena are under-used in clinical practice.